2022
DOI: 10.1021/acsomega.1c07087
|View full text |Cite
|
Sign up to set email alerts
|

Rock Damage Model Coupled Stress–Seepage and Its Application in Water Inrush from Faults in Coal Mines

Abstract: Mining-induced fractures often constitute water inrush channels, which lead to mine water inrush accidents. In this paper, a coupled model of stress–seepage–damage based on micromechanics is established, which simulates the initiation and propagation of cracks in rock materials and their interaction with fluid flow. The method combines the continuous damage model with the effective stress principle, in which the elastic modulus and permeability are related to the damage variables. The model is implemented via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In recent years, with the advancement of computer technology, more and more researchers use numerical simulation methods to study the phenomenon of fault water gushing. Using FEM to discretize faults is the most common method for studying water inrush disasters [17][18][19][20]. Yang W.M., et al [21] elucidated the process of water inrush in deep tunnels by establishing a finite element model.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advancement of computer technology, more and more researchers use numerical simulation methods to study the phenomenon of fault water gushing. Using FEM to discretize faults is the most common method for studying water inrush disasters [17][18][19][20]. Yang W.M., et al [21] elucidated the process of water inrush in deep tunnels by establishing a finite element model.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is the leading energy source in China and an important industrial raw material. , Many coal mines in China have complex geological conditions; the depth of mining has been increasing in recent years, and mine water disaster seriously restricts the safe and efficient production of coal mines, among which fault water disaster occurs in high frequencies, is highly invisible, and causes particularly severe harm. According to statistics, more than 80% of coal floor water inrush is caused by fracture structures such as faults. As a typical geological structure during mine production, the fault, with crack development in the coal and rock near them and damage to the native rock structure and its integrity, is very likely to become water channels between the aquifer and the coal seam under mining disturbance conditions, posing the threat of water disaster to mine production and even causing water inrush accidents, leading to economic losses and casualties . It can be seen that the fault water disaster is a severe threat to the safety of coal mine production, and it is necessary to conduct a series of studies on the fault permeability evolution and the retention of fault waterproof coal (rock) pillars.…”
Section: Introductionmentioning
confidence: 99%
“…10 − 16 As a typical geological structure during mine production, the fault, with crack development in the coal and rock near them and damage to the native rock structure and its integrity, is very likely to become water channels between the aquifer and the coal seam under mining disturbance conditions, posing the threat of water disaster to mine production and even causing water inrush accidents, leading to economic losses and casualties. 17 It can be seen that the fault water disaster is a severe threat to the safety of coal mine production, and it is necessary to conduct a series of studies on the fault permeability evolution and the retention of fault waterproof coal (rock) pillars.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies aimed at improving the wettability of coal seams and gas extraction efficiency concentrated on water injection and gas injection displacement. Research on water injection focused on the use of surfactants. Surfactants are the main wetting agents in improving wettability, and surface tension is a key parameter for their effectiveness. Jiang et al found that OP-10 surfactant solutions had the best effect on improving coal wettability based on surface tension and contact angle measurements of different wetting agents. , Several studies have explored the effect of wetting agents in different proportions or combined with other materials to improve the wettability of coal seams. , For instance, Zou et al added water-based SiO 2 nanofluids to the wetting agent solution and proposed a water injection method for coal seam improvement. , Molecular simulation software has been employed by some scholars to investigate the mechanism of surfactant effect on enhancing coal seam wettability. ,, In addition, the COMSOL simulation software was used to develop a coupled damage model during water injection to increase gas extraction rates. , Studies on gas injection displacement for improving gas extraction rates can be categorized into two types: using gases with strong adsorption capacity or gases that can break the dynamic balance of coal seam gas. CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology is essential to ensure energy security and achieve the “dual carbon” goal. This technology is crucial for achieving the low-carbon, clean, and efficient utilization of coal-based fossil energy.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 24 , 25 In addition, the COMSOL simulation software was used to develop a coupled damage model during water injection to increase gas extraction rates. 26 , 27 Studies on gas injection displacement for improving gas extraction rates can be categorized into two types: using gases with strong adsorption capacity or gases that can break the dynamic balance of coal seam gas. 28 30 CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology is essential to ensure energy security and achieve the “dual carbon” goal.…”
Section: Introductionmentioning
confidence: 99%